1-{(E)-[4-(4-Hydroxyphenyl)butan-2-ylidene]amino}-3-phenylthiourea: crystal structure, Hirshfeld surface analysis and computational study - Tan, Ming Yueh; Kwong, Huey Chong *; Crouse, Karen A.; Ravoof, Thahira Begum S. A.; Tiekink, Edward R. T. * (International Union of Crystallography, 2021)
The title thio-urea derivative, C17H19N3OS, adopts a U-shaped conformation with the dihedral angle between the terminal aromatic rings being 73.64 (5)°. The major twist in the mol-ecule occurs about the ethane bond with the Ci-Ce-Ce-Cb torsion angle being -78.12 (18)°; i = imine, e = ethane and b = benzene. The configuration about the imine bond is E, the N-bound H atoms lie on opposite sides of the mol-ecule and an intra-molecular amine-N-H⋯N(imine) hydrogen bond is evident. In the mol-ecular packing, hydroxyl-O-H⋯S(thione) and amine-N-H⋯O hydrogen bonding feature within a linear, supra-molecular chain. The chains are connected into a layer in the ab plane by a combination of methyl-ene-C-H⋯S(thione), methyl-ene-C-H⋯O(hydrox-yl), methyl-C-H⋯π(phen-yl) and phenyl-C-H⋯π(hy-droxy-benzene) inter-actions. The layers stack without directional inter-actions between them. The analysis of the calculated Hirshfeld surface highlights the presence of weak methyl-C-H⋯O(hydrox-yl) and H⋯H inter-actions in the inter-layer region. Computational chemistry indicates that dispersion energy is the major contributor to the overall stabilization of the mol-ecular packing.